Acute myelogenous leukemia in adolescents and young adults - Creutzig, Ursula; Kutny, Matthew A.; Barr, Ronald; Schlenk, Richard Friedrich; Ribeiro, Raul C. (Pediatric blood & cancer, 2018)
The incidence of acute myelogenous leukemia (AML) increases progressively with age. Favorable genetic mutations are most prevalent in children, and unfavorable profiles increase proportionately in adolescents and young adults (AYA) and into later adulthood. Survival rates of AYA have improved over recent decades to 50-60%, but their accrual to clinical trials remains poor. In contrast to AYA with acute lymphoblastic leukemia, the prognostic benefit for AYA with AML enrolled in pediatric compared with adult trials is minor and only seen when different protocols are used. The distinctive needs of AYA, including intensive psychological services, call for their treatment within specialized centers that offer complex supportive care.
First published: 18 April 2018
Gesehen am 02.07.2019